Prevalence of Child Sexual Abuse among Public School Students in Janakpurdham, Nepal - Dahal , Laxmi; Pandey, Smita; Sah, Shiwani; Yadav, Poonam Kumari (Journal of Biratnagar Nursing Campus, 2025)
Background :Child Sexual Abuse is any kind of sexual contact with a child under the age of 18. Sexual abuse can be physical or non-physical. Sexual abuse is one of the commonest and serious public issues affecting millions of people each year over the world. One in every five children around the world is suspected of suffering from sexual abuse. Child Sexual abuse has negative physical as well as psychological impact and persists over time to majority. This study aimed to identify the prevalence of Child Sexual Abuse among public academy scholars in Janakpurdham.Methods: A descriptive cross-sectional study design was used to assess prevalence of Child sexual abuse among 213 academy scholars of Janakpurdham. Complete enumeration method was used to achieve required sample size.A semi-structured self-administered questionnaire was used for data collection. Descriptive and inferential statistics were used to dissect data; chi-square test was used to find out association between child sexual abuse and socio- demographic variables.Results : Nearly one- fourth (24.4%) of respondents had endured Child Sexual Abuse, among them half of the respondents (50%) had experienced Child Sexual Abuse in public places. Likewise, 48% of the respondents revealed about the offence with their friend circle (72%). Nearly half of the respondents felt scared (42.3%) as an immediate effect and further than half of the respondents endured anxiety (59.6%) as a late effect of Child Sexual Abuse. There was association of Child sexual abuse with age, gender, grade of children and exposure to media.Conclusion: The study concluded that child sexual abuse is one of the commonest offences among adolescent girls. Nearly one fourth of respondents endured child sexual abuse in their life.